2021
DOI: 10.1002/cac2.12157
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death ligand‐1 regulates angiogenesis and metastasis by participating in the c‐JUN/VEGFR2 signaling axis in ovarian cancer

Abstract: Background Although programmed cell death‐ligand 1 (PD‐L1) plays a well‐known function in immune checkpoint response by interacting with programmed cell death‐1 (PD‐1), the cell‐intrinsic role of PD‐L1 in tumors is still unclear. Here, we explored the molecular regulatory mechanism of PD‐L1 in the progression and metastasis of ovarian cancer. Methods Immunohistochemistry of benign tissues and ovarian cancer samples was performed, followed by migration, invasion, and angiogenesis assays in PD‐L1‐knockdown ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…The cytotoxic effects of apatinib might lead to the reduction of total VEGFR2 in NSCLC cells. It is reported that multiple signaling pathways and molecules might be involved in the regulation of VEGFR2 expression [46][47][48]. Our previous study also indicated that apatinib suppressed lung cancer stem-like properties by inactivation of β-catenin signaling, which might further lead to the downregulation of VEGF and its receptor VEGFR2 [49].…”
Section: Discussionmentioning
confidence: 96%
“…The cytotoxic effects of apatinib might lead to the reduction of total VEGFR2 in NSCLC cells. It is reported that multiple signaling pathways and molecules might be involved in the regulation of VEGFR2 expression [46][47][48]. Our previous study also indicated that apatinib suppressed lung cancer stem-like properties by inactivation of β-catenin signaling, which might further lead to the downregulation of VEGF and its receptor VEGFR2 [49].…”
Section: Discussionmentioning
confidence: 96%
“…reported that PD-L1 promotes angiogenesis in ovarian cancer through the c-Jun/VEGFR-2 signaling axis. Furthermore, a combination of the PD-L1 inhibitor durvalumab plus Apatinib enhanced the anti-angiogenesis effect and inhibition of cell migration and invasion ( 38 ). These findings suggested that synergy between Apatinib and immunosuppressants does not merely involve a single pathway and that Apatinib may work synergistically with immunosuppressive agents in the treatment of retroperitoneal liposarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is beneficial to normal cells, but in tumors, it helps malignant cells adjust and adapt to adverse conditions, allowing them to develop and continue to grow. In addition, the PD-1/PD-L1 signaling pathway plays a key role in tumor function and survival (55,56). Autophagy is influenced by the PD-L1 ligand.…”
Section: Autophagymentioning
confidence: 99%